PENGARUH KEPEMIMPINAN DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DI DINAS PENDIDIKAN KABUPATEN KLATEN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Murwani, Liestyawati Sri; -, Mulyanto - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2012)
ABSTRACT The aim of this research are to test the influences of the leadership, the competence, on the performance of officers with the motivation as an intervening variable at Dinas Pendidikan Kabupaten Klaten. Data was collected from 116 officers as a sample. It was collected directly with a questioner and observation. Tools of analysis such as Path analysis with t test, F test, determination coefficient test are used in this reseach: The t test also prove that the leadership influential positive and not significant on the motivation at Dinas Pendidikan Kabupaten Klaten. The competence influential positive and significant on the motivation at Dinas Pendidikan Kabupaten Klaten. The leadership influential negative and not significant on the performance of officers at Dinas Pendidikan Kabupaten Klaten. The competence influential positive and significant on the performance of officers at Dinas Pendidikan Kabupaten Klaten. The motivation influential positive and significant on the performance of officers at Dinas Pendidikan Kabupaten Klaten. F test or simultaneous influential the leadership, the competence and the motivation on the performance of officers at Dinas Pendidikan Kabupaten Klaten. Determination test (R2 test) shows that dependent variable can be cleared by the leadership, the competence and the motivation that be researched for the fist and second of equation of double linear regression about 55,9% and 44,1% be cleared out side of variable. Keywords: the leadership, the competence, the performance of officers and the motivation.